Evaluating spray gelation and spray freeze drying as the granulation method to prepare oral tablets of amorphous drug nanoplex - Chua, Angeline (2023)
Amorphous drug nanoplex represents one of the most promising solubility enhancement strategies of poorly-soluble drugs. Solubility enhancement capability of nanoplex hitherto has been demonstrated for nanoplex suspension and lyophilized/spray-dried nanoplex, but not for its oral tablets. Using ciprofloxacin as the model poorly-soluble drug, we investigated spray gelation (SG) of alginate and spray freeze drying (SFD) with cryoprotective mannitol, as the nanoplex's granulation methods. Both granules were evaluated in terms of their morphology, physical form, flowability, drug content, preparation yield, dissolution profile, drug solubility enhancement, and storage stability. Subsequently, tablets of the granules were prepared and characterized in terms of their drug content uniformity, weight variation, friability, hardness, dissolution profile, and solubility enhancement. The results showed that nanoplex in SG granules was embedded in dense amorphous alginate matrix, while nanoplex in SFD granules was dispersed in porous crystalline mannitol particles. Despite their distinct morphology, physical form, and dissolution profile, the two granules exhibited similar drug solubility enhancements. Both granules were readily compacted into tablets with minimal changes in their dissolution and solubility enhancement after tableting. The present work demonstrated SG and SFD as viable granulation methods of nanoplex, with SG granules exhibiting superior flowability, stability, but lower yield.